Myeloidcells in the immunosuppressive microenvironment in glioblastoma: The characteristics and therapeutic strategies - Huang, Boyuan; Zhang, Jin; Zong, Wenjing; Chen, Sisi; Zong, Zhitao; Zeng, Xiaojun; Zhang, Hongbo (Frontiers in Immunology, 2023)
Glioblastoma (GBM) is the most common and lethal malignant tumor of the central nervous system in adults. Conventional therapies, including surgery, radiotherapy, and chemotherapy, have limited success in ameliorating patient survival. The immunosuppressive tumor microenvironment, which is infiltrated by a variety of myeloid cells, has been considered a crucial obstacle to current treatment. Recently, immunotherapy, which has achieved great success in hematological malignancies and some solid cancers, has garnered extensive attention for the treatment of GBM. In this review, we will present evidence on the features and functions of different populations of myeloid cells, and on current clinical advances in immunotherapies for glioblastoma.